Genotype‐phenotype correlation of KATP channel gene defects causing permanent neonatal diabetes in Indian patients. Issue 1 (15th September 2020) - Gopi, Sundaramoorthy; Kavitha, Babu; Kanthimathi, Sekar; Kannan, Alagarsamy; Kumar, Rakesh; Joshi, Rajesh; Kanodia, Swati; Arya, Archana Dayal; Pendsey, Sanket; Pendsey, Sharad; Raghupathy, Palany; Mohan, Viswanathan; et al.
Abstract: Background: There are very few reports pertaining to Indian patients with neonatal diabetes mellitus (NDM). Activating or gain of function mutations of KATP channel genes namely KCNJ11 and ABCC8 are most predominant cause of permanent neonatal diabetes mellitus (PNDM). Objectives: To identify the genotype‐phenotype correlation of KATP channel gene defects in a large series of (n = 181) Indian PNDM patients. Methods: Direct sequencing of all exons of KCNJ11 and ABCC8 genes in all 181 patients with PNDM were performed. Clinical and biochemical data were collected. Results: We have identified the molecular basis of KATP ‐NDM in 39 out of 181 patients (22%). Of these, 20 had KCNJ11 mutations and 19 had ABCC8 mutations, thus comprising 51% of KCNJ11 and 49% of ABCC8 . There were four novel mutations (D1128Tfs*16, Y1287C, S1422T, and H1537R) in ABCC8 gene. Three patients with KCNJ11 mutations had developmental delay with DEND syndrome. In patients with ABCC8 mutations developmental delay was seen in seven out of 19 (36.8%). Of this, three patients (15.7%) had DEND phenotype and four (21%) had iDEND. Of the 39 patients, 33 (84%) patients were shifted to sulfonylurea therapy (glibenclamide). Of this, 19(57.5%) patients harbored KCNJ11 mutations and 14(42.1%) ABCC8 mutations. Conclusions: This is the first largest study in NDM patients in India demonstrating the importance of KATP channel gene mutation screening in PNDM and efficacy of glibenclamide for Indian patients with KATP ‐PNDM. The success rate of transfer is more in patients with KCNJ11 mutations compared with those with ABCC8 mutations.